Various Word Shorts in the Podcast of Political Figures Sandiaga Uno: Corpus-Based Analysis - JR, Vicno Triwira Dhika; Rizal, Teuku Thifly Fakhrur (Institute of Humanities and Education Studies (IHES), 2023)
This study aims to examine the use of abbreviation in the political figure Sandiaga Uno's podcast. This research will also bring up the use of corpus linguistics which is very effective in research in the field of linguistics, especially abbreviation or shortening of words. This type of research is a descriptive qualitative research. The advanced method which is the main approach of this research is the corpus linguistic method. Corpus linguistics can be interpreted as research that relies on linguistic data analysis using digital technology. The data in this study were collected using documentation techniques and utilizing the KORTARA (Korpus Nusantara) application which originates from the Wawancara Tokoh Indonesia corpus. Research data in this study will be analyzed using the KORTARA application. Analysis using the KORTARA application can be referred to as computational linguistics, because it utilizes corpus linguistics applications. The work steps of this computational linguistic analysis start from identifying data, classifying data, interpreting data, and drawing conclusions. The findings of this study reveal that the use of abbreviations in the video podcast of political figure Sandiaga Uno can be in the form of abbreviations, acronyms, and fragments. This research reveals that the most dominant type of abbreviation used in the podcast is fragment. The results of the data analysis also revealed that there were no types of abbreviations for letter symbols and contractions, this was based on the theme or discussion in the video which was not too focused on economic issues, but politics. The findings of abbreviation data in this study also reveal that the use of abbreviated or abbreviated language will continue to be used by political figures, in order to build better and more familiar communication with their interlocutors.